Acute Decompensation in Pediatric Cardiac Patients: Outcomes After Rapid Response Events. Issue 5 (May 2017) - Bavare, Aarti C.; Rafie, Kimia S.; Bastero, Patricia X.; Hagan, Joseph L.; Checchia, Paul A.
Abstract : Objective: We studied rapid response events after acute clinical instability outside ICU settings in pediatric cardiac patients. Our objective was to describe the characteristics and outcomes after rapid response events in this high-risk cohort and elucidate the cardiac conditions and risk factors associated with worse outcomes. Design: A retrospective single-center study was carried out over a 3-year period from July 2011 to June 2014. Setting: Referral high-volume pediatric cardiac center located within a tertiary academic pediatric hospital. Patients: All rapid response events that occurred during the study period were reviewed to identify rapid response events in cardiac patients. Interventions: None. Measurements and Main Results: We reviewed 1, 906 rapid response events to identify 152 rapid response events that occurred in 127 pediatric cardiac patients. Congenital heart disease was the baseline diagnosis in 74% events (single ventricle, 28%; biventricle physiology, 46%). Seventy-four percent had a cardiac surgery before rapid response, 37% had ICU stay within previous 7 days, and acute kidney injury was noted in 41% post rapid response. Cardiac and/or pulmonary arrest occurred during rapid response in 8.5%. Overall, 81% were transferred to ICU, 22% had critical deterioration (ventilation or vasopressors within 12 hr of transfer), and 56% received such support and/or invasive procedures within 72 hours. Mortality within 30 days post event was 14%. Significant outcome associations included: single ventricle physiology—increased need for invasive procedures and mortality (adjusted odds ratio, 2.58; p = 0.02); multiple rapid response triggers—increased ICU transfer and interventions at 72 hours; critical deterioration—cardiopulmonary arrest and mortality; and acute kidney injury—cardiopulmonary arrest and need for hemodynamic support. Conclusions: Congenital heart disease, previous cardiac surgery, and recent discharge from ICU were common among pediatric cardiac rapid responses. Progression to cardiopulmonary arrest during rapid response, need for ICU care, kidney injury after rapid response, and mortality were high. Single ventricle physiology was independently associated with increased mortality.